Reciprocal Relation between Spin Peltier and Spin Seebeck Effects - Alessandro Sola; Vittorio Basso; Michaela Kuepferling; Carsten Dubs; Massimo Pasquale (Proceedings, 2019)
In recent times, the interaction between magnetization and heat currents in a magnetic material has gained a renewed interest thanks to the observation of the spin Seebeck effect (SSE) [1,2]. [...]